A randomized controlled interventional study for analgesic effects of intrathecal versus intravenous dexmedetomidine on subarachnoid anesthesia with hyperbaric bupivacaine - Manu Dadhwal; Anupama Gupta; Ajay Kurian (Asian Journal of Medical Sciences, 2025)
Background: Various pharmacologic agents such as opioids, benzodiazepines, ketamine, and alpha2 adrenergic agonists are commonly used to increase the duration of subarachnoid block. Alpha2 agonists have analgesia and sedative properties when used as adjuvant in regional anesthesia. Stable hemodynamics and decreased oxygen requirement due to enhanced sympathoadrenal stability make them very useful adjuvants. Aims and Objectives: To evaluate the effects of intrathecal versus intravenous (IV) dexmedetomidine on the block, characteristics, and sedation in patients receiving subarachnoid block with hyperbaric bupivacaine. Materials and Methods: In this prospective, randomized controlled, double-blind study total of 90 patients with the American Society of Anesthesiologists grade I and II were randomly allocated into three groups: Group A (n=30) received IV 20 mL 0.9% NaCl over 10 min followed by intrathecal 2.4 mL 0.5% hyperbaric bupivacaine+0.2 mL normal saline, group B (n=30) received IV 20 mL 0.9% NaCl over 10 min followed by intrathecal 2.4 mL 0.5% hyperbaric bupivacaine+0.2 mL (5 mcg) dexmedetomidine, and group C (n=30) received IV dexmedetomidine 1 mcg/kg in 20 mL 0.9% NaCl over 10 min followed by intrathecal 2.4 mL 0.5% hyperbaric bupivacaine+0.2 mL normal saline. Results: The mean time for two-segment regression in group A was 100.57±4.24 min, in group B it was 193.3±7.07 min, and in group C was 170.23±3.53 min. The duration of sensory and motor block was prolonged in groups B and C. The Visual analog scale scores were comparatively higher in group A than in groups B and C. The Sedation score in group C was significantly higher as compared to groups A and B. Conclusion: Both intrathecal and IV dexmedetomidine prolong the effect of intrathecal hyperbaric bupivacaine, improves post-operative analgesia, and provides arousable sedation without causing hemodynamic instability.